Ottawa classification for symptomatic acetabular dysplasia assessment of interobserver and intraobserver reliability. Issue 5 (May 2020) - Bali, K.; Smit, K.; Ibrahim, M.; Poitras, S.; Wilkin, G.; Galmiche, R.; Belzile, E.; Beaulé, P. E.
Abstract : Aims: The aim of the current study was to assess the reliability of the Ottawa classification for symptomatic acetabular dysplasia. Methods: In all, 134 consecutive hips that underwent periacetabular osteotomy were categorized using a validated software (Hip2Norm) into four categories of normal, lateral/global, anterior, or posterior. A total of 74 cases were selected for reliability analysis, and these included 44 dysplastic and 30 normal hips. A group of six blinded fellowship-trained raters, provided with the classification system, looked at these radiographs at two separate timepoints to classify the hips using standard radiological measurements. Thereafter, a consensus meeting was held where a modified flow diagram was devised, before a third reading by four raters using a separate set of 74 radiographs took place. Results: Intrarater results per surgeon between Time 1 and Time 2 showed substantial to almost perfect agreement among the raters (κappa = 0.416 to 0.873). With respect to inter-rater reliability, at Time 1 and Time 2 there was substantial agreement overall between all surgeons (Time 1 κappa = 0.619; Time 2 κappa = 0.623). Posterior and anterior rating categories had moderate and fair agreement at Time 1 (posterior κappa = 0.557; anterior κappa = 0.438) and Time 2 (posterior κappa = 0.506; anterior κappa = 0.250), respectively. At Time 3, overall reliability (κappa = 0.687) and posterior and anterior reliability (posterior κappa = 0.579; anterior κappa = 0.521) improved from Time 1 and Time 2. Conclusion: The Ottawa classification system provides a reliable way to identify three categories of acetabular dysplasia that are well-aligned with surgical management. The term 'borderline dysplasia' should no longer be used. Cite this article: Bone Joint Res. 2020;9(5):242–249.